Survey Kondisi Fisik Atlet Panjat Tebing Ukm Mpa Jonggring Salaka Universitas Negeri Malang - Assiddicky, Muhammad Jimly; Fadhli, Nurul Riyad (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
In the last five years the rockclimbing athletes of UKM MPA Jonggring Salaka have experienced a decline in championship achievements. This can be seen from the participation of rockclimbing athletes UKM MPA Jonggring Salaka in several competitions that did not achieve results. It is necessary to have literacy or reference data to develop special programs provided by the coach in order to improve the physical condition of rockclimbing athletes UKM MPA Jonggring Salaka State University of Malang. This study used a total sample of 15 athletes using a survey approach method and included a quantitative descriptive research design. Instruments used in physical condition tests 1) Strength: Grip Strength Dynamometer, Push Up, Sit Up; 2) Endurance: Flexed- Arm Hang, Harvard Step; 3) Power: Vertical Jump; 4) Flexibility: Sit and Reach; 5) Balance: Stork Stand. Dominant and non- dominant hand strength was good for both males and females. Shoulder muscles were good for males and poor for females. Abdominal muscles were good for both genders. Arm endurance of male athletes is very good, females lacking. Cardiovascular endurance was poor for both. Male leg muscles good, female fair. Abdominal and back flexibility good, body balance fair for both genders